Corporate Social Responsibility in the Universities - Onditi, Arvinlucy (Core, 2016)
This article is meant to shed light on how universities and other Not-Profit organizations can use Corporate Social Responsibility (CSR) to market their organization and improve their image. With a wake of globalization and online learning, students who are university customers have several options of universities to join hence for any university to survive, it must work on its competitive strategies and they must get it right first time and all the time. Hence this article recommends that the starting point for any university is CSR which is a principle that has been ignored for a long time in the institutions of higher learning as well as the NPO. A time has come when these institutions must show their relevancies to the society in which they do business. This article is recommending a CAID strategy, that is, Create A Difference day). This strategy must be incorporated in the organizations culture and because the institutions of higher learning have different cohorts coming in different periods, it is recommended that the projects be carried out every semester. It should be noted that little is much, it all depends with the intent of the person doing it. Organizations should adopt feedback mechanism and monitor their progress before and after using this strategy.
Keywords: Corporate Social Responsibility; Marketing tools; Universities; Create An Impact Day (CAID); Strategy; Competitors; Non-Profit Organization (NPO) and Environment